Anatomical study for leaves and Epidermal properties in Athionema R.BR. species (Brassicaceae) in Iraq. - Al-ibrahemi, Safa; Al-shemarri, D.Khalil (Iraqi Journal of Science, 2023)
The research included anatomical study of nine wild species of the genusAthionema R.BR. from BrassicaceA family in Iraq, and these species are:A.arabicum (L.), A.carneum (Banks et sol.),A. cordifolium (DC.), A.fimbriatum(Boiss.),A. froedinii (Rech. F.), A. speciosum (Boiss. et Huet), A. syriacum(Boiss.),A. grandiflorum (Boiss. et Hoh.) , A.trinervium (D.C.).The researchcovered the anatomical characteristic of the leaf Epidermis as well as leavesvenation, also transvers sections for leaves were studied ,and revealed that someanatomical characteristics have taxonomic importance in distinguishing the species.This research also showed the presence of important variations in internal charectersfor leaves anatomy as it was characterized as Bifacial and variation between thePalisade layer and spongy layer in term of their cell thickness ,as some species weredistinguish by interfering of palisade and spongy layer .The study also showeddifferences in stomatal complexes pattern , and the characteristics that related to theshapes of the Epidermal cells of leaf and leaf venaition have also importanttaxonomic and diagnostic value in the species under study.